Pengembangan Alat Pengecekan Suhu Tubuh dan Hand Sanitizer Otomatis Reysikom 2.0 Guna Pencegahan Penularan Covid-19 - Enno Febra Wardani; Andi Agustinus; Muhammad Husein; Arifh Suganda; Sandy Dwi Cahyo; Mia Hera Yanti (Universitas Harapan Medan, 2021)
Corona Virus Deases 2019 (Covid-19), currently, has become a global pandemic.Precautionaltrials of the virus spreading are conducted by washing hands and body-temperature checking frequently. Varius automatic body-temperature checking and hand-washing tools had been marketed widely. Unfortunately, in local community level, both tools are still separated equipment, and even still scarce. Those functions (body-temperature checker and hand sanitizer) in an integrated one toolare needed especially in common places like a university. The presence of Raysikom 2.0 strives torespond the mentioned challenges. This developed deviceis intended to depress the spreading of Covid-19 in local level. The device was developed through an experimental process. It was conducted on September to October 2021 in the Computer Engineering System Laboratory, Bina Insan University – Lubuklinggau. Constructing components of the devices consist of physical components (electronic compartments, container, and frames as well as casing), design, coding and assembling parts. Some main electronical components constructed from Arduino Uno, Ultrasonic Sensor (HC-SR04), Non-Contact Temperature Sensor (mlx90614), pump, mp3, and LCD. The device was developed using fiveprocesses of making such as analysis of needs, mechanical design (hardware), coding, testing, analysis, and interpretation. Results of this research indicate that the established electronical system and testing of Raysikom 2.0 is run well. This device has been utilized in the campus of Bina Insan University to depress spreading of Covid-19 during office hours.